Conservative management of intravesical erosion of a synthetic mid-urethral sling for the treatment of stress urinary incontinence, based on patient preference: A case report - M. O'Kane; G. Araklitis; A. Rantell; D. Robinson; L. Cardozo (Elsevier, 2022)
Background: Intravesical mesh erosion is an uncommon late complication of placement of a synthetic mid-urethral sling (MUS) for the treatment of stress urinary incontinence, and only a few cases have been reported. Optimal management remains controversial, though there is a tendency toward surgical removal through a variety of routes. However, surgical removal comes with its own risks and is not necessarily associated with an improvement in symptoms. We, herein present the first case of a conservatively managed intravesical mesh erosion following MUS placement. Case: Nine years after insertion of a tension-free vaginal tape (TVT), a patient presented with persistent lower abdominal pain and dysuria. Flexible cystoscopy demonstrated an erosion of the tape through the bladder wall. The patient declined surgical intervention at the time. Therefore, she was commenced on regular methenamine hippurate and vaginal oestrogen, and kept under surveillance with regular cystoscopies. Her symptoms responded to this treatment and 6 years later remained well controlled on this regime. Conclusion: This case demonstrates that conservative management may be a safe and appropriate option for patients who decline surgical excision of mesh erosion.